Effects of larval diets and temperature regimes on life history traits, energy reserves and temperature tolerance of male Aedes aegypti (Diptera: Culicidae): optimizing rearing techniques for the sterile insect programmes - Sasmita, Hadian Iman; Tu, Wu-Chun; Bong, Lee-Jin; Neoh, Kok-Boon (Parasites & vectors, 2019)
Producing high quality sterile males is vital in Aedes aegypti rear-and-release birth control strategies. Larval diets, rearing temperatures, and their interactions determine the accumulation rates of essential nutrients in larvae, but these factors have been understudied in relation to mass-rearing techniques for producing eminent males. We compared the effects of two larval diets, a cereal-legume-based diet (Khan's diet) and a standard larval diet developed in the FAO/IAEA Insect Pest Control Laboratory (IAEA 2 diet). Diets were tested at selected temperatures for both larval and male adult life history traits, adult extreme temperature tolerance, and mating capacity relative to energy reserves of reared male adult Ae. aegypti. Khan's diet resulted in shorter immature development time at each test temperature (except for 25 °C) than an IAEA 2 diet. Larvae reared at 28 °C and 32 °C with Khan's diet demonstrated low pupation rates (c.80%). We accounted for these phenomena as secondary sex ratio manipulation, because a higher proportion of male adults emerged at 28 °C and 32 °C than that for the IAEA 2 diet. In general, the pupal development time shortened as temperature increased, resulting in higher teneral energy reserves in male mosquitoes. High energy reserves allowed male mosquitoes reared with Khan's diet to have higher adult longevity (5-6 days longer when sugar-fed and 2-3 days longer when water-fed) and tolerance of heat stress than those fed on the IAEA 2 diet. The IAEA 2 diet produced larger male mosquitoes than Khan's diet did: mosquitoes fed on Khan's diet were 1.03-1.05 times smaller than those fed on the IAEA 2 diet at 28 °C and 32 °C. No evidence indicated reduced mating capacity for small mosquitoes fed on Khan's diet. Larvae reared at 28 °C and 32 °C with Khan's diet were characterized by shorter immature development time compared with those fed on the IAEA 2 diet. Adult mosquitoes produced from that larval rearing condition exhibited a significant male bias, long lifespan, and better endurance against extreme temperatures relative to energy reserves. Thus, the larval diet at rearing temperature of 28 °C and 32 °C optimized rearing techniques for the sterile insect programmes. However, mating competitiveness and flight performance of adult males require further investigation.